Harmony-Scatter Search to Solve Travelling Salesman Problem - Al-Obaidi, Ahmed (Iraqi Journal of Science, 2024)
This paper presents a hybrid metaheuristic algorithm which is Harmony-Scatter Search (HSS). The HSS provides Scatter Search (SS) with random exploration for search space of problem and more of diversity and intensification for promising solutions. The SS and HSS have been tested on Traveling Salesman Problem. A computational experiment with benchmark instances is reported. The results demonstrate that the HSS algorithm produce better performance than original Scatter Search algorithm. The HSS in the value of average fitness is 27.6% comparing with original SS. In other hand the elapsed time of HSS is larger than the original SS by small value. The developed algorithm has been compared with other algorithms for the same problem, and the result was competitive with some algorithm and insufficient with another.